The effects of the built environment on the general health, physical activity and obesity of adults in Queensland, Australia. (November 2021) - Wang, Siqin; Liu, Yan; Lam, Jack; Kwan, Mei-Po
Highlights: Built environment factors are quantified by GIS-based methods in 5D dimensions: design, density, diversity, destination and distance Physical activity is positively associated with general health and negatively associated with the prevalence of obesity Built-environment factors have direct effects on physical activity but indirect effects on general health and obesity. Low-density and car-dependent neighbourhoods can be activity-friendly to mitigate obesity if they provide easy access to green space. Education promoting changes to daily routines and lifestyle to consciously take advantage of activity-supporting built environments should be a part of the health intervention measures for obesity prevention. Abstract: The built environment has been identified as a key factor for health intervention and obesity prevention. However, it is still unclear to what extent the built environment is associated with obesity and general health and to what extent such an association is mediated through variation in physical activity. This study aims to examine the associations between individual characteristics, the built environment, physical activity, general health and body mass index to reveal the pathways through which the built environment is associated with the prevalence of obesity. Using data from 1, 788 adults aged 18 to 65 in Queensland from Wave 16 of the Household, Income, and Labour Dynamics in Australia survey, we use geographic information system-based methods to quantify built environment factors in 5D dimensions: Density, Diversity, Design, Distance and Destination accessibility . We then employ multi-level mixed-effect models to test the hypothesised relationships between individual characteristics, the built environment, physical activity, general health and body mass index. The results indicate that physical activity is positively associated with general health and negatively associated with the prevalence of obesity. Adjusting for individual characteristics, we find that built-environment factors have direct effects on physical activity but indirect effects on general health and obesity. Among these factors, greater green space exposure plays a key role in enhancing general health and reducing obesity. Low-density and car-dependent neighbourhoods can be activity-friendly and mitigate obesity if these neighbourhoods are also equipped with easy access to green space.